ARTIFICIAL FEATURES OF EDUCATION IN DESCRIPTION OF THE 20TH CENTURY - Колосніченко, О. В.; Пашкевич, К. Л.; Лозко, Ю. Я. (Art and Design, 2019)
Analysis and generalization of scientific and practical developments in the aesthetic-harmonic design of special-purpose clothing: features of forming and means of compositional expressiveness. For the analysis of literary sources of information, the literary-analytical method was used; for the analysis of visual sources - the visual-analytical method. The method of deduction (conclusions about the process of forming uniforms for workers of coal and mining mines) and incomplete induction (manifestations of compositional expression) were used. The practical developments and conceptual provisions of the activity of constructivist artists in the creation of clothes for labor are considered. The situation in the field of designing overalls in the territory of the Ukrainian SSR and the USSR as a whole has been investigated. The characteristic of changes in the form of overalls, intended for workers of coal mining and mining mines during 1920-1980 years was received. The overalls are considered as an art object and analyzed the manifestations of possible means of compositional expressiveness, the principles of combining forms in suits of various special purpose. The means of compositional expressiveness and the volume-spatial form of special purpose clothes from the position of visual perception are systematized. The modification of the form of overalls made during the 1920-1980 years for workers of coal mining and mining mines during the period was investigated. The obtained results of the research give an opportunity to form an idea of the aesthetic component in the general concept of special purpose clothes and to supplement the available theoretical information in this field. Also, the findings of the study may serve as an additional informative source at the stage of artistic-constructive analysis in modern design engineering not only the class of industrial clothing, but also domestic.